2004
DOI: 10.1068/p5288
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Scene Layout from Optical Contact, Shadows, and Motion

Abstract: Kersten et al (1997 Perception 26 171-192) found that the perceived motion of an object in a 3-D scene was determined by the motion of a shadow. In the present study, we compared the effect of a shadow to that of a second object on the ground in determining the perceived position in depth of a floating object in both dynamic and stationary scenes. Changing the second (lower) object from textured to dark increased the influence of the second object on the judged position of the first object. Giving the second o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 18 publications
(19 reference statements)
7
33
0
Order By: Relevance
“…Our results concur with those of an increasing number of studies in recent years demonstrating the importance of the ground surface in scene perception (e.g., Feria et al, 2003;Meng & Sedgwick, 2001Ni et al, 2004Ni et al, , 2005Ni et al, , 2007Ooi et al, 2001;Sinai et al, 1998;. Future studies are needed to examine the relative influence of type of surface (ground vs. ceiling) and location in the visual field in other visual tasks, such as visual search and absolute and relative distance judgments.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our results concur with those of an increasing number of studies in recent years demonstrating the importance of the ground surface in scene perception (e.g., Feria et al, 2003;Meng & Sedgwick, 2001Ni et al, 2004Ni et al, , 2005Ni et al, , 2007Ooi et al, 2001;Sinai et al, 1998;. Future studies are needed to examine the relative influence of type of surface (ground vs. ceiling) and location in the visual field in other visual tasks, such as visual search and absolute and relative distance judgments.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, they found that (1) optical contact information dominated motion parallax when only one object was presented, whereas optical contact could be outweighed by a grouping effect with multiple objects moving rigidly (Ni et al, 2005); (2) the perceived distance of an object was determined both by optical contact information and by information provided by shadow, with shadow having a greater effect, especially in moving scenes (Ni et al, 2004); and (3) the addition of occlusion information limited the range of perceived distance of an object indicated by optical contact and motion parallax (Ni et al, 2007). Sinai et al (1998) found that with a gap or a change of texture on the ground surface, perceived distance was less accurate than when the ground surface was continuous.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis suggested that both processes interact by cumulating their effects on variable S and that the former process (depth induction) appears to be stronger than the latter (reverse projection). Recent studies on depth vision (e.g., He, Wu, Ooi, Yarbrough, & Wu, 2004;Madison et al, 2001;Ni, Braunstein, & Andersen, 2004 have examined the interaction of processes relating to optical contact and other factors of perceptual depth, such as occlusion, shadows, and motion parallax. The comparative evaluation we made may be viewed as an item to be added to this set of results, since the depth induction process we discussed essentially involves the optical contact condition.…”
Section: Discussionmentioning
confidence: 99%